(untitled) (Fiep Bulletin - online, 2012)
Understand that all revolves around teaching practice involves entering the curriculum in the different looks thatunderlie the curriculum theory, taking into account that the curriculum is framed around relationships within and outside theschool, where each of them influences the formation of a professional. However, in the training of graduates practical stage as akey element to make teachers has been reduced to a simple intervention that looks at the conceptual-theoretical fade into theroutine of the class. Thus, as the University of Cundinamarca transversal proposal, implemented into the training of graduates inphysical education activities centered curriculum for understanding and introducing a facilitator creating element, which hasenabled its development differently dimensioned as to see and do in physical education teaching.